Educação sexual e sexualidade no discurso de uma pessoa com deficiência visual - Maia, Ana Cláudia Bortolozzi [UNESP] (My University, 2011)
Sexuality and sex education for visually impaired people are still a few subjects studied in the field of Education. The aim of this study was to investigate sexuality and sex education of the visually impaired, through an interview with an adult woman, blind from birth, for further analysis of thematic content. It is a descriptive-qualitative case study. The following categories were described in the results: (1) Concept of sexuality, (2) Sexual Education, (3) Sexuality and Disability, (4) Social issues and prejudice. The data confirm other studies showing the existence of social prejudice, sexual myths, no sex education or sex education with superficial information and difficulties predominantly psychosocial and not organic in relation to sexuality. We conclude that sexuality and sex education are important issues that should be considered in the general education of people with disabilities.

A sexualidade e a educação sexual de pessoas com deficiência visual são ainda temas poucos estudados no campo da Educação. O objetivo deste estudo foi investigar a sexualidade e educação sexual de deficientes visuais, por meio de uma entrevista com uma mulher adulta, cega de nascença, para posterior análise de conteúdo temática. Trata-se de uma pesquisa descritiva-qualitativa, tipo estudo de caso. As seguintes categorias foram descritas nos resultados: (1) Conceito de sexualidade, (2) Educação Sexual, (3) Deficiência e Sexualidade, (4) Questões sociais e preconceito. Os dados obtidos ratificam outros estudos evidenciando a existência de preconceito social, mitos sexuais, educação sexual omissa ou com informações superficiais e dificuldades predominantemente psicossociais, e não orgânicas, em relação à sexualidade. Conclui-se que a sexualidade e a educação sexual são questões importantes que devem ser consideradas na educação geral de pessoas com deficiências.
Sex education and sexuality in the speech of a person with visually impaired
Keywords: Sexuality; Sex education; Visually impaired; Sexualidade; Educação sexual; Deficiência visual